Konsumerisme dan Hegemoni Barat terhadap Masyarakat Negara Berkembang: Perspektif Antonio Gramsci - Fansuri, Hamzah (Center for Integrative International Studies Laboratory, Faculty of Political and Social Sciences, UIN Sunan Ampel Surabaya, 2017)
This article elaborates dominant discourse in contemporary international relations study which is especially focus on how consumerism as ideology and the machine of capitalism operate until become Western cultural hegemony to the developing countries. By using Antonio Gramsci’s perspective, this research is on qualitative approach with literature study method. The argument built in this research is that society and culture will always change with the influences that exist in the world today. These changes can be happen in a fast or slow time. On a large or small scale in everyday life, so that people are unconsciously in a circle of domination and hegemony. However, this research is not a comparative study between different time periods, but a study of the identification of influences that play an important role in transforming and shaping cultural aspects and the people way of life in the majority of developing countries. Therefore this research aims to describe and dismantle consumerism as a Western cultural hegemony in influencing the culture of society and reflect social reality in the post-industrial era and neoliberal globalization.